Identification and characterization of immature Anopheles and culicines (Diptera: Culicidae) at three sites of varying malaria transmission intensities in Uganda - Musiime, Alex K.; Kilama, Maxwell; Otto, Geoffrey; Kyagamba, Patrick; Nankabirwa, Joaniter I. (Malaria journal, 2020)
Over the last two decades, there has been remarkable progress in malaria control in sub-Saharan Africa, due mainly to the massive deployment of long-lasting insecticidal nets and indoor residual spraying. Despite these gains, it is clear that in many situations, additional interventions are needed to further reduce malaria transmission. The World Health Organization (WHO) has promoted the Integrated Vector Management (IVM) approach through its Global Vector Control Response 2017–2030. However, prior roll-out of larval source management (LSM) as part of IVM, knowledge on ecology of larval aquatic habitats is required.